2019
DOI: 10.3892/ijmm.2019.4369
|View full text |Cite
|
Sign up to set email alerts
|

Influence of radiation exposure pattern on the bone injury and osteoclastogenesis in a rat model

Abstract: Radiotherapy, one of the clinical treatments of cancer, is accompanied by a high risk of damage to healthy tissues, such as bone loss and increased risk of fractures. The aim of the present study was to establish a rat model of local and systemic bone injury by focal irradiation, in order to study the etiological mechanism and intervention. The proximal metaphyseal region of the left hindlimb of male Sprague-Dawley rats were exposed to a single 2 Gy or three 8 Gy doses delivered on days 1, 3 and 5 using a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 32 publications
(52 reference statements)
1
25
0
Order By: Relevance
“…During the whole study period each animal received a cumulative radiation dose of approximately four Grey. In this context, Zhai et al were able to demonstrated that a bony impairment in rats, caused by a single dose of two Grey irradiation, is reversible and will presumably recover completely 53 . Based on the score sheets course of study, no radiation related effects were noticed.…”
Section: Discussionmentioning
confidence: 99%
“…During the whole study period each animal received a cumulative radiation dose of approximately four Grey. In this context, Zhai et al were able to demonstrated that a bony impairment in rats, caused by a single dose of two Grey irradiation, is reversible and will presumably recover completely 53 . Based on the score sheets course of study, no radiation related effects were noticed.…”
Section: Discussionmentioning
confidence: 99%
“…IR induced bone loss is thought to be caused by increased osteoclastogenesis in response to radiation induced osteocyte death (Zhang, 2018). However, in vitro studies have shown that osteoclastogenesis was accelerated at relatively low-dose, but inhibited at higher doses of irradiation (Zhang, 2017, Zhai, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Zhai et al showed that the damage of bone tissue in rats, caused by a single dose of two Grey irradiation, is reversible and it is likely to recover completely. 30 Based on the score sheets we were able to control the general well-being of the animals. No radiation related effects were noticed.…”
Section: Discussionmentioning
confidence: 99%